N-Propargylation of secondary amines directly using calcium carbide as an acetylene source. (1st June 2017) - Fu, Rugang; Li, Zheng
A one-pot N-propargylation of secondary amines has been achieved by heating the amine with formaldehyde and calcium carbide in DMSO in the presence of CuCl as a catalyst. Fifteen examples of propargylic tertiary amines, 12 of which are novel, were efficiently prepared in yields of 65–84%. The advantages of the method are broad substrate scope and a simple work-up procedure.